Perspectivism of knowing and genealogy of interpreting in Nietzsche. For a hermeneutic theory of figurativeness [Spanish] (2012)
The present article locates the figurative character of the hermeneutics in the thinking of Neitzsche. For this, it is necessary to have a particular perspective that makes a character (a real, literary, historical or philosophical one, etc.) a figure of interpretation that neither shows things metaphysically nor it is directed towards them by means of a phenomena. Instead, it revives them symbolically, inspiring a new wave of hermeneutics for interpretation and a new angle for comprehension. The main function is its relatedness as a background on which the imperceptible connection stands out. That makes a hermeneutic figure the center or an axis of vibrations that move its discursive and critical components, crossing with impertinence the boundaries of the interpreted and the imaginary.